Autonomous Drug Discovery with Parallel Intelligence - Lin, Fei; Yang, Jing; Sun, Dali; Kovacs, Levente; Wang, Fei-Yue (IEEE/CAA journal of automatica sinica, 2025)
Dear Editor, The 2024 Nobel Prize in Chemistry was awarded to David Baker, Demis Hassabis, and John Jumper, recognizing their groundbreaking contributions to protein design and the prediction of complex protein structures [1]. This accomplishment advances the frontier of "Artificial Intelligence (AI) for Science". It marks a milestone in studying complex systems, highlighting a shift in scientific exploration from traditional causal inference to a comprehensive approach centered on solving complex system problems.